Electrostatic aspects of adsorption on silica and titania surfaces - Lobanov, V. V.; Chuiko, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2001)
The influence of outer electric field of the ionic crystal surface layer on the structure of adsorption complexes is examined and their role in the run of physicochemical processes at the solid-gas interface is studied. Taking into account of the subsurface electric field has been shown to allow to predict the structure of primary adsorption complexes, to estimate the energetics of the transformations of molecules at solid surfaces, and to determine properties of the surface compounds formed.